Perspectives Generation Z On The Fomo Trend In Kintamani, Bali - Evi Wijayanti, Ni Putu; Darmiati, Made; Prabasavika, Made Gita; Citra Maharani, Ni Kadek (Journal of Business on Hospitality and Tourism, 2024)
The development of Changes in new trends in alpha tourism has become a significant phenomenon in society after the COVID-19 pandemic, especially Generation Z who is quite active in following this trend. The phenomenon of FOMO or Fear of Missing Out, the hesitation to miss out on experiences or information, has emerged as an issue among Generation Z, especially in the context of visits to popular tourist destinations such as Kintamani, Bali. Tourism is a sector that has a significant economic impact with a variety of activities that attract tourists, including natural, cultural and culinary exploration. Generation Z in Indonesia plays an important role in this trend, showing the phenomenon of Fear of Missing Out (FOMO) in popular tourist attractions such as Kintamani, Bali. The problem that arises is how Generation Z perceives and responds to this FOMO phenomenon, and how it affects their travel behavior. The purpose of this study is to investigate and analyze Generation Z's views and responses to this FOMO trend. This research uses a qualitative method approach, involving data collection techniques through tringulation techniques. Hopefully, the results of this study can provide a clear picture and broaden the understanding of Generation Z's response and perception towards FOMO, as well as its impact on their traveling trends.